Implikasi Pemahaman pengguna Software OLIBS 724 bagi pegawai Bank NTB Syariah terhadap loyalitas nasabah - I Putu Kariasa; Riduan Mas’ud; Muhamad Yusup (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
This study aims to identify the understanding of OLIBS (Online Integrated Banking System) 724 Core banking Software users and its implications for customer loyalty of NTB Syariah banks. The research method used in this study is qualitative research, namely in-depth data processing with data from observations, interviews, and literature. Direct interviews were conducted with key informants such as officials and technical employees of the Information System Technology division of Bank NTB Syariah, front liner administrative employees of Bank NTB Syariah, and customers of Bank NTB Syariah. The result of this study is that human resources are the main asset and play an essential role for NTB syariah banks, and need to constantly be improved in skills and performance. Bank NTB Syariah needs to place training on the use of OLIBS 724 software as essential in improving the knowledge and performance of its employees (both old and new employees) so that employees can adjust to any conditions. Quality of service must start with customer needs and end with customer satisfaction. Satisfied customers get value from Islamic bank products, the value of fairness for profit sharing as expected, the value of service quality, and the value of the system or something religious emotion, which is to avoid usury. The results of this study show that employee understanding of OLIBS 724 software users positively influences customer satisfaction. The more employees understand the use of OLIBS 724 software, the more customers will be served well and quickly, which in turn will increase customer satisfaction and loyalty